2017
DOI: 10.18203/2394-6040.ijcmph20171319
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of sexually transmitted infections in a district hospital from Himachal Pradesh

Abstract: Background: Sexually transmitted infections (STIs) are a public health problem, which increase the HIV transmission and are a burden to the individual, his family and community. The prevalence of STIs varies widely across different regions in our country. There is immense need to study the pattern of STIs in various regions for proper planning and implementation of control strategies. The study was conducted with the objective to assess the pattern of STIs and their prevalence in a District hospital of Himacha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…14 In a study done in Himachal Pradesh, genital scabies is reported only on 4.2% of patients. 11 The second most common STI in our study was candidal balanoposthitis (16.4%) in males followed by candidal vaginal discharge (12.5%) in females. It is similar to study done by Goel et al 15 It shows increasing trends of fungal infections.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…14 In a study done in Himachal Pradesh, genital scabies is reported only on 4.2% of patients. 11 The second most common STI in our study was candidal balanoposthitis (16.4%) in males followed by candidal vaginal discharge (12.5%) in females. It is similar to study done by Goel et al 15 It shows increasing trends of fungal infections.…”
Section: Discussionmentioning
confidence: 53%
“…10 Also, a study done in Himachal Pradesh on pattern of STI's in a district hospital reported 25-44 to be the most common age group. 11 This indicates that STI's are higher in sexually active age group and thus their education can lead to tremendous decrease in incidence as well as prevalence of STI's.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] and Sharma et al . [ 15 ] noting greater (20% and 33.33%, respectively). VC was seen in 11.89% of patients which was greater than that reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 7 9 11 12 14 15 ] Anogenital warts were the next common viral STD at 13.52% compared to the previous reports, with the prevalence ranging from 0.98% to 17.5%. [ 6 7 9 11 12 14 15 ] The prevalence of genital MC was on the higher side at 9.28%, with earlier studies reporting a much lesser prevalence. [ 6 7 12 14 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation